POLICY INTEGRATION OF POST-MARRIAGE COUNSELLING IN ISLAMIC FAMILY EDUCATION IN THE DISTRICT OF PENUKAL ABAB LEMATANG ILIR - Eka Saputra, Darwin; Yuniar, Yuniar; Handayani, Tutut; Toriano Pentang, Jupeth (Conciencia, 2025)
This study evaluates the policy integration of post-marriage counselling within Islamic family education in the District of Penukal Abab Lematang Ilir. The study is motivated by the increasing incidence of domestic conflict and divorce in the region, which highlights the need for preventive and educational family policies. Employing a qualitative research design, this study applies the CIPP (Context, Input, Process, Product) evaluation model to examine policy implementation and outcomes comprehensively. Data were collected through in-depth interviews, participant observation, and document analysis involving key stakeholders, including the Head of the Office of Religious Affairs (KUA), married couples participating in post-marital counselling programs, and local policymakers. Data analysis was conducted through thematic analysis, involving data reduction, categorization, and interpretation aligned with the CIPP components. The findings indicate that post-marital counselling contributes positively to enhancing couples’ understanding of marital rights and obligations, communication skills, and family conflict management from an Islamic educational perspective. Nevertheless, the program’s effectiveness remains limited by short implementation duration, inadequate human and institutional resources, and low participant engagement in follow-up sessions. This study recommends strengthening interactive counselling methods, enhancing facilitator capacity, and improving inter-institutional policy synergy to reinforce Islamic family resilience and ensure the sustainability of post-marital counselling integration.